Heat Responsive Solar Shading In Double Skin Façade For Tropical Climates - Yonghuort, Lim (2024)
Double skin façade (DSF) has emerged as a pivotal strategy for enhancing thermal performance and energy efficiency in office buildings, particularly in tropical climates. However, the full aptitudes of DSF have yet to be realized, and energy savings may not be substantial. This study investigates the potential of DSF for building thermal enhancement and energy saving, incorporating heat-responsive solar shading using thermo-bimetal louvers in the thermal cavity of DSF in Köppen-classified tropical climates. The research adopts calculation and computational simulation, EnergyPlus software. Findings indicate that both single skin façade (SSF) and DSF perform differently in respective tropical climate categories, influencing the thermal and energy performance of DSF accordingly. However, the DSF of each tropical climate group has the potential to enhance thermal performance in buildings with slightly varying annual energy efficiency rates. The study also reveals that the shading device significantly impacted the thermal and energy performance of DSF. Furthermore, thermo-bimetal louvers within the DSF cavity not only reduce the need for artificial light in DSF but also improve its thermal performance and energy efficiency. Overall, a well-designed DSF with the integration of heat-responsive solar shading has the capacity to enhance thermal behavior and energy efficiency in terms of both cooling and lighting in office buildings in tropical climates.